PERANCANGAN DAN PENGEMBANGAN ALAT PEMOTONG STYROFOAM SEMI OTOMATIS MENGGUNAKAN METODE RULA DI DESA KALISARI - Nur Syafiq; Enty Nur Hayati (Jurnal Ilmiah Dinamika Teknik, 2020)
One of the UKM loans issued is adequate equipment. This happened in an effort to cut Styrofoam in the village of Kalisari Semarang, which still uses cutters in the Styrofoam cutting process. To overcome this problem, a study was carried out to design a Styrofoam making tool that can help the Styrofoam cutting process.The design of the tool uses Anthropometry and economic analysis as well as work analysis with the RULA method. Anthropometric data used are elbows in the sitting position, stretches of hands forward, stretches of hands to the side, height of popliteal. The data that has been obtained is then tested for data uniformity, data sufficiency test, and percentile selection. The result of the RULA score when cutting Styrofoam manually is 7 with a high level of risk that needs to be taken now.The results of this study consist of work facilities that use semi-automatic styrofoam. Analysis of work posture with the RULA method produces a RULA score of 3 with a small level. Aids try on the Styrofoam cutting area, and produce tools that can be used quite well, cutting workers that can be done easily and neatly. This tool can also help in cutting Styrofoam compared to the previous manual process. Keywords: RULA, Anthropometry, Product Design, Ergonomics